101 secrets for your twenties eaudiobook - Angone, Paul (Tantor Media, 2016)
Every twenty-something needs a little black book of secrets. Our twenties are filled with confusion, terrible jobs, anticipation, disappointment, cubicles, break-ups, transition, quarter-life crisis, loneliness, post-college what the heck , moderate success sandwiched between complete failure. We need a worn and weathered guide stashed somewhere close by to help shed some light on this defining decade. That guide is this book. Expanded from the blog post "21 Secrets for Your 20s" that spread like Internet wildfire with nearly a million readers in 190 countries, 101 Secrets for Your Twenties will encourage, inspire, prompt a plethora of LOLs, and kick-start your life forward with its witty, honest, and hilarious wisdom-stuffed pearls to help you rock life in your twenties.